Predicting pool safety habits and intentions of Australian parents and carers for their young children. (December 2019) - Hamilton, Kyra; Peden, Amy E.; Smith, Stephanie; Hagger, Martin S.
Highlights: Normative factors predicted deliberate (intentions) action of pool safety behaviors. Normative factors also predicted more automatic (habits) action. Planning and anticipated regret predicted habits for restricting and supervising. Perceived barriers were associated with behavior for supervising behaviors only. Restricting access may be governed by more habitual than intentional processes. Abstract: Introduction: Children under five years are most at risk of experiencing fatal and nonfatal drowning. The highest proportion of drowning incidents occur in private swimming pools. Lapses in adult supervision and failures in pool barriers are leading contributory factors for pool drowning in this age group. Methods: We investigated the role of the theory of planned behavior social cognitions (attitude, subjective norm, and perceived behavioral control) as well as perceived barriers, planning, role construction, and anticipated regret on parents' and carers' intentions and habits toward two pool safety behaviors: restricting access and supervising children around private swimming pools. The study adopted a cross-sectional correlational design. Participants ( N  = 509) comprised Australian parents or caregivers with children aged under five years and access to a swimming pool at their residence. Participants completed a battery of self-report measures of social cognitive variables with respect to the swimming pool safety behaviors for their children. Results: Path analytic models controlling for past behavior indicated that subjective norm, planning, anticipated regret, and role construction were important predictors of habit, and subjective norm was a consistent predictor of intentions, for both behaviors. Planning predicted intentions in the restricting access sample, while attitudes, barriers, and role construction also predicted intentions in the supervising sample. Both models controlled for past behavior. Conclusion: Current findings indicate the importance of psychological factors for restricting access and supervising behaviors, with normative factors prominent for both reasoned (intentions) and non-conscious (habits) behavioral antecedents. It seems factors guiding restricting access, which likely require regular enactment of routine behaviors (e.g., ensuring gate is not propped open, pool fence meets standards), may be governed by more habitual than intentional processes.